INVESTIGATION IMIDAZOLINE DERIVATIVES OBTAINED FROM SYNTHETIC PETROLEUM ACIDS AS CORROSION INHIBITOR (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Imidazoline derivatives have been synthesized based on the synthetic petroleum acids (SPA) and diethylentriamine. Complexes were prepared from these compounds and HCl in ratio 1:1, 1:2, 1:3. 20% solution of the complexes were prepared in aqueous isopropyl alcohol. The kinetic effect of steel corrosion in 1% NaCl solution saturated with CO2 were studied ACM Gill AC potentiometer. It was found that, the imidazoline derivatives complexes based on the SPA and DETA with HCl in molar ratio 1:1 of 25 ppm concentration protection from corrosion is 83,5%, 100 ppm  concentration – 97,1%; the proportion of 1:2 complex of  25 ppm – 82,8%, 100 ppm  concentration – 97,3%, but in the case of the 1:3 complex shows the best result - 94 and 98,8%.